Developing of corrosion resistance nano copper oxide coating on copper using anodization in oxalate solution - -, Suryanto; Mahmood, Mahmood Hameed; Hazza Faizi Al Hazza, Muataz; Haider I., Farag (International Journal of Engineering, 2018)
The excellent heat transfer properties of copper it is the reson behind its use in the manufacturing of various equipment of heat transfer applications. However, contamination of water by copper in water circulation systems is one of the serious industrial problems [1]. This contamination commonly results from copper corrosion reactions in boiler feed water environment. The contamination of copper could be reduced by improving copper corrosion resistance in water. This research studies the developing of copper corrosion resistant by using anodization technique. The anodization experiments are conducted in oxalate solutions of concentrations from 0.1 to 0.5 M, at a temperature range from 24 to 0 οC and applied potential from 7.5 to 9 V. Anodized coating was analyzed using field emission scanning microscope, energy dispersive X-ray spectroscopy, and X-ray diffraction. Characterization results referred to the formation of copper oxide anodized coating with grain size range from 25 to 68 nm. The tests of the corrosion resistance of the anodized copper samples were carried out in simulated boiler feed water. The results show the enhancement of corrosion resistance of anodized samples. The corrosion protection efficiencies for the anodized coating increased 86.2% and 74.5% in testing solutions contains 3.5% NaCl, and 2 mg/l NH3, respectively.